2023
DOI: 10.2147/ijn.s398802
|View full text |Cite
|
Sign up to set email alerts
|

Smart Chondroitin Sulfate Micelles for Effective Targeted Delivery of Doxorubicin Against Breast Cancer Metastasis

Abstract: Introduction Metastasis is a major challenge in breast cancer therapy. The successful chemotherapy of breast cancer largely depends on the ability to block the metastatic process. Herein, we designed a dual-targeting and stimuli-responsive drug delivery system for targeted drug delivery against breast cancer metastasis. Methods AS1411 aptamer-modified chondroitin sulfate A-ss-deoxycholic acid (ACSSD) was synthesized, and the unmodified CSSD was used as the control. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…7d). In addition, compared with the PBS, PYT NPs, NIR groups, the results of hematoxylin-eosin (H&E) and Ki67 staining (H&E and Ki67 staining method refers to previous reports [67][68][69][70][71]) showed that the tumor tissue in PYT NPs + NIR group disappeared at 12 days after irradiation, only connective tissue and granulation tissue were observed in irradiation region (Fig. 7e).…”
Section: Resultsmentioning
confidence: 72%
“…7d). In addition, compared with the PBS, PYT NPs, NIR groups, the results of hematoxylin-eosin (H&E) and Ki67 staining (H&E and Ki67 staining method refers to previous reports [67][68][69][70][71]) showed that the tumor tissue in PYT NPs + NIR group disappeared at 12 days after irradiation, only connective tissue and granulation tissue were observed in irradiation region (Fig. 7e).…”
Section: Resultsmentioning
confidence: 72%
“…7d). In addition, compared with the PBS, PYT NPs, NIR groups, the results of hematoxylin-eosin (H&E) and Ki67 staining (H&E and Ki67 staining method refers to previous reports [45][46][47]) showed that the tumor tissue in PYT NPs + NIR group disappeared at 12 days after irradiation, only connective tissue and granulation tissue were observed in irradiation region (Fig. 7e).…”
Section: Resultsmentioning
confidence: 74%
“…The clinical application of nanoplatforms has been restricted due to significant concerns regarding their toxicity. 71 In order to address this issue, three major parameters, including body weight changes, pathological toxicity, and systematic distribution of treatment agents, were analyzed to assess the toxicity and biosafety of candidate formulations in immunocompromised C57BL/6 mice. Throughout the treatments, no significant weight loss was observed in all experimental groups (Fig.…”
Section: Radiosensitivity Increased the Apoptotic Cell Deathmentioning
confidence: 99%